2017
DOI: 10.1590/0100-69912017003010
|View full text |Cite
|
Sign up to set email alerts
|

Hemorroidopexia por grampeamento parcial: aspectos clínicos e impacto sob a fisiologia anorretal

Abstract: RESUMO Objetivo: avaliar o impacto na fisiologia anorretal da hemorroidopexia por grampeamento parcial, das complicações relacionadas à técnica cirúrgica, dor e sangramento pós-operatório e recidiva de doença hemorroidária após um ano de cirurgia. Métodos: estudo prospectivo, descritivo, em pacientes consecutivos, portadores de doença hemorroidária do tipo mista ou interna, com componente interno classificado como grau III ou IV, submetidos à hemorroidopexia por grampeamento parcial. Resultados: foram estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
2
1
1
Order By: Relevance
“…These numbers may be regarded as high but may also be easily understood because of the limitation for carrying heavy loads at work after cholecystectomy and inguinal hernia repair. However, return to work was described after 4-19 days after outpatient anorectal surgery [13,14]. This is in contrast to the present study where one out of 3 patients only was not able to return to work at POD30.…”
Section: Discussioncontrasting
confidence: 99%
“…These numbers may be regarded as high but may also be easily understood because of the limitation for carrying heavy loads at work after cholecystectomy and inguinal hernia repair. However, return to work was described after 4-19 days after outpatient anorectal surgery [13,14]. This is in contrast to the present study where one out of 3 patients only was not able to return to work at POD30.…”
Section: Discussioncontrasting
confidence: 99%
“…Our preliminary data had shown similar clinical efficacy between the PSH and CSH procedures for advanced hemorrhoidal prolapse over a medium-term follow-up with less postoperative pain and fewer cases of initial fecal urgency in the PSH-treated patients. 12 The PSH procedure showed little impact on anorectal physiology with low complications, consistent with the finding by Soares et al 13 Favorable outcomes with PSH have been reported in short-term follow-up case series. 1315 However, a head-to-head comparison between PSH and CSH in randomized trial has not been made, and information on long-term outcomes is lacking.…”
supporting
confidence: 85%
“…12 The PSH procedure showed little impact on anorectal physiology with low complications, consistent with the finding by Soares et al 13 Favorable outcomes with PSH have been reported in short-term follow-up case series. 1315 However, a head-to-head comparison between PSH and CSH in randomized trial has not been made, and information on long-term outcomes is lacking. Our choice of a noninferiority trial design was based on the expectation that the PSH procedure is noninferior to CSH with fewer postoperative complications.…”
supporting
confidence: 85%
“…Hemorrhoidal veins are typically characterized by dilated, thin-walled vessels within the submucosal arteriovenous plexus [ 55 ]. Typical complaints associated with HD include pain, bleeding, pruritis, burning, and swelling [ 56 ]. Patients that have symptomatic internal hemorrhoids may complain of itching, bleeding, pain, burning, prolapse, mucus discharge, moisture, swelling or difficulty with perianal hygiene [ 57 ].…”
Section: Hemorrhoidsmentioning
confidence: 99%